A retrospective review (audit) of gynaecological emergency surgery at Groote Schuur Hospital for the period of January to December 2019 - Hlako, Tebogo Clive (Department of Obstetrics and Gynaecology, 2025)
Background. Gynaecological emergencies are a common cause of morbidity and mortality among women of reproductive age worldwide. There is less audit done on the burden of emergency surgery in developing countries. Objectives. The planned study analysed the clinical processes and outcomes of gynaecological emergency surgeries performed at a tertiary level hospital in the Western Cape (Groote Schuur) in the year 2019. Methods. The study was a retrospective descriptive record review of patients who underwent emergency surgery at Groote Schuur Hospital. Data was captured manually and electronically using theatre data base. Statistical analysis was performed using SPSS Statistics for Windows 2021. Results. We analysed 290 completed women records. The mean age was 30.16, with 230 (79.3%) women of reproductive age. There were 234 (79.1%) pregnancy related surgical procedures done. The most common occurrence among pregnancy related surgeries was ectopic pregnancy, accounting for 112 (47.9%) cases. A total of 130 (44.8%) women had anaemia and 125 (43.1%) had a tachycardia prior to surgery. Twenty-seven (9.3%) women were in hypovolaemic shock before surgery. A total of 179 (61.7%) women had the surgery 4 hours after being booked in theatre. Only 46 (15.9%) women accessed surgery within 2 hours. Twenty (6.9%) women had to wait for more than 24 hours for their operation to be done. The most common reason for the 24-hour delay, accounting for 85% (N=17), was the lack of emergency theatre time, as other cases from different disciplines were given priority. There were 42 (14.5%) women with complications post operatively and no mortality recorded. Conclusion. The study indicates good outcomes for emergency gynaecological surgeries performed at Groote Schuur Hospital in 2019. However, significant delays between the decision for surgical intervention and the actual performance of the surgeries were highlighted. The delays in hypovolaemic women were attributed to the need to compete with other surgical disciplines for emergency theatre time.